2019
DOI: 10.3390/nu11040713
|View full text |Cite
|
Sign up to set email alerts
|

Usability and Engagement Evaluation of an Unguided Online Program for Promoting a Healthy Lifestyle and Reducing the Risk for Eating Disorders and Obesity in the School Setting

Abstract: Implementing integrated online prevention to reduce the risk of both obesity and eating disorders, in the school setting, is a promising approach. The challenge is to develop highly user-friendly and motivating programs, to foster adherence and effectiveness. The purpose of this study was to evaluate the usability of such a universal prevention program for students aged 14–19 years, and to address engagement issues. A mixed-methods approach was chosen, consisting of a think-aloud task, a semi-structured interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…This study design has been used by multiple usability studies in the areas of clinical and health informatics. [29][30][31] The SUS has also been used to evaluate interactive visualizations. 32,33 Since the study focused on user feedback rather than expert feedback on the dashboards, heuristic evaluation 34 was not considered.…”
Section: Study Conductionmentioning
confidence: 99%
“…This study design has been used by multiple usability studies in the areas of clinical and health informatics. [29][30][31] The SUS has also been used to evaluate interactive visualizations. 32,33 Since the study focused on user feedback rather than expert feedback on the dashboards, heuristic evaluation 34 was not considered.…”
Section: Study Conductionmentioning
confidence: 99%
“…On the other hand, an effective treatment for bulimia nervosa or BED, such as cognitive behavior therapy, did little to improve metabolic physical health status in a randomized controlled trial by Mathisen et al [15]. Nitsch et al [16] concluded the Special Issue with a report on how to improve engagement in a new, online, integrated prevention program that addresses eating, weight, and mental health of adolescents called “Healthy Teens @ School”.…”
Section: Treatments Addressing Co-morbidity and Integrated Carementioning
confidence: 99%
“…Blending online and offline learning content within a curriculum is considered more valuable than online learning alone [71]. Studies show that in educational institutions the possibility of using a web-based health program during teaching time and not only during leisure time is a crucial factor for regular usage [72,73]. The integration of web-based measures into everyday school life can reduce barriers to use, e.g., low motivation [74].…”
Section: Discussionmentioning
confidence: 99%
“…Against the background of the known high drop-out rates, in-depth analyses of the perception and usability of web-based measures for potential users are necessary. The Technology Acceptance Model [97] or the System Usability Scale [73] offer possible approaches. Also, no intended engagement use was predefined [98,99], as the intervention was not designed with a strict modular structure, e.g., in the sense of a teaching series.…”
Section: Limitationsmentioning
confidence: 99%